Pelatihan Pemanfaatan Sampah Buah Menjadi Pupuk Cair Organik bagi Ibu-ibu PKK Kalurahan Murtigading Sanden Bantul - Salamah, Siti; Hakika, Dhias Cahya; Sulistiawati, Endah; Amelia, Shinta; Rahmadewi, Yunda Maymana (Indonesia Berdaya, 2022)
Consumption of fruit is highly recommended to keep the body healthy. In line with increasing public awareness of fruit consumption, the amount of fruit waste also increases. One way to reusing fruit waste is to convert it into liquid organic fertilizer (LOF). A group of female senior citizen (PKK) from  Murtigading Village, Sanden, Bantul participated a workshop on making LOF reactors in the form of stacked buckets as an effort to convert fruit waste into plant fertilizer. LOF is made from fruit waste that is put into a stacked bucket reactor. The entire process takes two months to produce leachate, which is then aerated for one month before being used. The participants were pleased about the workshop and learned about the benefits of LOF 80% and how to make LOF 84%.